Interactive Learning Exchange : Exploring Strategies to Reach and Work with Adolescents - Kennedy Elder, Leslie (World Bank, Washington, DC, 2013)
The Millennium Development Goals (MDGs) have refocused global attention on still unaddressed needs of children and youth. In response to the MDGs, the World Bank is strengthening its attention to the most vulnerable populations such as children and adolescents, through a cross-sectoral approach to human development including education, health, nutrition, sexual and reproductive health, and social protection. One crucial component for healthy adolescent development is good nutrition. It affects health, learning, physical fitness and the ability to withstand stress. Yet this population has received little emphasis in nutrition programs, and nutrition, in turn, has received little attention from programs for youth. While some low-cost solutions to adolescent malnutrition are available, nutrition specialists and programs do not have the operational experience needed to access and work with youth. In order to learn from the experience of adolescent health and development specialists, and avoid reinventing the wheel, the World Bank Nutrition team hosted a consultation to explore best practice strategies for reaching and working with youth. The objectives of the workshop were (i) to gather and distill information from multiple sectors on the successful approaches and promising practices for identifying, reaching, and working with vulnerable adolescents in resource-poor settings; and (ii) to discuss how effective strategies from other sectors might be exploited for nutrition. The Learning Exchange resulted in dialogue between a diverse group of adolescent health and development and nutrition sector specialists that would not otherwise have occurred. It successfully raised awareness among youth specialists of the synergies between actions to address the healthy development of adolescents and improved nutrition. The consultation also streamlined the learning process for the nutrition sector about how to work with this age group.